2022
DOI: 10.57178/jer.v5i2.364
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Fraud Through Forensic Accounting, Audit Investigation and Auditor Professionalism

Abstract: This study aims to analyze the effect of the application of forensic accounting, investigative audits, and auditor professionalism on fraud disclosures at the BPKP office representing the province of South Sulawesi. This study used primary data by conducting direct research in the field by providing questionnaires to 35 auditors from the BPKP office representing South Sulawesi Province. The statistical method used is multiple linear regression analysis with the help of SPSS software. The results of the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Other studies have demonstrated that forensic accounting services aid in detecting financial fraud. For example, Abdulrahman et al (2020), Rifani andHasan (2022), andJarallah andAl-Sayed (2022) found that forensic accounting helps identify fraud indicators during financial statement audits and enhances understanding of financial and accounting issues. Al Enazi et al (2022) investigated the effectiveness of forensic accounting techniques in detecting financial fraud and the level of forensic accounting practice in the Kingdom of Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have demonstrated that forensic accounting services aid in detecting financial fraud. For example, Abdulrahman et al (2020), Rifani andHasan (2022), andJarallah andAl-Sayed (2022) found that forensic accounting helps identify fraud indicators during financial statement audits and enhances understanding of financial and accounting issues. Al Enazi et al (2022) investigated the effectiveness of forensic accounting techniques in detecting financial fraud and the level of forensic accounting practice in the Kingdom of Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accountants who are characterized by a high level of motivation show a higher work and life satisfaction. A high level of motivation is therefore in itself valuable for accountants and a decrease in motivation might affect them negatively (Rifani and Hasan 2022). According to Dunham (1984), motivated employees are happy, committed, and are continually looking for ways to improve their performance, on the other hand, demotivated employees often have low productivity and high turnover rates.…”
Section: Motivationmentioning
confidence: 99%